PENINGKATKAN PRESTASI BELAJAR PKn MENGGUNAKAN TEKNIK PENCATATAN MIND MAP BAGI SISWA KELAS VI B SD 1 BANTUL - Umi Fatonah (Dinas Pendidikan, Pemuda dan Olahraga DIY, 2016)
The purpose of the research was to practice the mind map writing technique in order to improve the students’ score of the six grade students of Bantul 1 Elementary School.